Effect of Alkali and Alkaline Earth Metal Chlorides on Cellobiose Decomposition in Hot-Compressed Water - Yu, Yun; Mohd Shafie, Zainun; Wu, Hongwei (American Chemical Society, 2015)
This paper reports a systematic study on the catalytic effect of alkali and alkaline earth metal (AAEM) chlorides on cellobiose decomposition in hot-compressed water (HCW) at 200–275 °C. The AAEM chlorides catalyze the cellobiose decomposition in HCW in the order of MgCl2 > CaCl2 > KCl > NaCl. The presence of AAEM chlorides not only increases the reaction rate but also alters the selectivities of primary reactions of cellobiose decomposition. The isomerization reactions to cellobiulose and glucosyl-mannose are strongly promoted by these cations due to their interactions with cellobiose. The hydrolysis reaction to glucose is also promoted as the hydrolysis of hydrated metal complexes generates H3O+. However, the promotion effect on hydrolysis reaction is much weaker, resulting in reduced glucose selectivity in AAEM chloride solutions. Depending on the AAEM species, the secondary decomposition reactions of those primary products are selectively catalyzed in AAEM chloride solutions, thus greatly influencing the product distribution of cellobiose decomposition in HCW.